(untitled) (Grande Medical Journal, 2024)
Sarcoma botyroides (Rhabdomyosarcoma) of the uterus is not a common disease. Here we describe a case of 14 yr old young girl, she came to the emergency (ER) department of our hospital with acute retention of urine and per vaginal bleeding on and off. Her MRI and biopsy confirmed sarcoma botryoides. She was planned for surgery. We performed a Total laparoscopic Hysterectomy with Bilateral Salpingoophorectomy with removal of upper vagina.